Efficacy of acupuncture in experimental intracerebral hemorrhage: a systematic review and meta-analysis - Wu, Zhe; Jiao, Mingyuan; Wang, Tianqi; Zhang, Baiwen; Dong, Hao; Du, Yunpeng; Yao, Jiayong; Zou, Wei (Frontiers in Neurology, 2024)
Objective: There is currently a lack of evidence in evidence-based medicine regarding acupuncture treatment for experimental intracerebral hemorrhage (ICH). The aim of this study was to systematically evaluate the efficacy of acupuncture treatment for experimental ICH based on neurological function scores and brain water content (BWC). Methods: Eight mainstream Chinese and English databases were searched. Outcome measures included neurological function scores and BWC, and subgroup analysis was conducted based on study characteristics. Results: A total of 32 studies were included. Meta-analysis results indicated that compared to the control group, the acupuncture group showed significant reductions in mNSS (MD = -3.16, p < 0.00001), Bederson score (MD = -0.99, p < 0.00001), Longa score (MD = -0.54, p < 0.0001), and brain water content (MD = -5.39, p < 0.00001). Subgroup analysis revealed that for mNSS, the autologous blood model (MD = -3.36) yielded better results than the collagenase model (MD = -0.92, p < 0.00001), and simple fixation (MD = -3.38) or no fixation (MD = -3.39) was superior to sham acupuncture (MD = -0.92, p < 0.00001). For BWC, the autologous blood model (MD = -7.73) outperformed the collagenase model (MD = -2.76, p < 0.00001), and GV20 -GB7 (MD = -7.27) was more effective than other acupuncture points (MD = -2.92, p = 0.0006). Conclusion: Acupuncture significantly improves neurological deficits and brain edema in experimental ICH. Acupuncture at GV20 -GB7 is more effective than at other points. These findings support further studies to translate acupuncture into clinical treatment for human ICH. The registration number for PROSPERO is CRD42023435584.